PENGARUH KEPEMIMPINAN DAN MOTIVASI TERHADAP KEPUASAN KERJA DI POLSEK KALIBANTENG - Untung Widodo (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2012)
Organization is built and running among the environment. Organizations cannot control the environment around it, instead organizations should always adaptive to environment change. Thr research goal is to analyze the influence of leadership on job satisfaction in Polsek Kalibanteng, to analyze the influence of motivation on job satisfaction in Polsek Kalibanteng, and to analyze the influence of leadership and motivation on job satisfaction in police Kalibanteng. The research uses explanatory research, population in this study were all police officers of Kalibanteng as many as 86 person. Data analysis tools used in this research are validity test, reliability test, the classic assumption test, multiple regression analysis, hypothesis testing, and the determination coefficient. These results is there is a significant positive effect on job satisfaction leadership in police officers of Kalibanteng, it is proved from the results of the calculation of t-count (5.458)> t-table (1.663) or sig t (0.000) < 0.05, hence Ho refused and Ha are accepted, there is a significant positive effect of motivation on job satisfaction in police officers Kalibanteng, it is proved from the results of the calculation of t-count (4.283)> t-table (1.663) or sig t (0.000) <0.05, hence Ho refused and Ha ma are accepted, there is a significant positive effect between Leadership and Motivation on job satisfaction in police officers of Kalibanteng, it is known from the calculation of F-count ( 64.023)> F-table (3.107) or sig F (0,000) <5%, hence Ho refused and Ha are accepted and the coefficient of determination is equal to 0.597, which means the variation changes in police officer of Kalibanteng job satisfaction are influenced by Leadership and Motivation for about 59.7%, while the remaining 40.3% is influenced by other factors outside the study. So, the leadership and motivation are the dominant factor affecting officers job satisfaction.